Cybersecurity and Cyber Defense Insights: The Complementary Conceptual model of Cyber resilience (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2023)
Cybersecurity planning within a complex system and applying its principles aims to achieve system resilience in cyberspace. The purpose of a complex system is to carry out a mission as a set of abilities and preferences concerning the internal and external circumstances of the system. Achieving cyber resistance requires organizational, human, material, and financial resources to implement measures, activities, and procedures to reduce residual (remaining) security risk. This part of the security risk must be accepted within the system since it is impossible to achieve its further reduction. The research in this paper analyzes ways and means to achieve cyber resistance in the conditions of today's growing security risks. This research aims to create a new model of cyber resistance, which includes cyber and information security. This also considers that the methods of separating previously unseen threats and attacks of the past day are unknown today in a large number of business cases. To confront the challenges, there is a need to create "knowledge about ignorance" and the development of cyber capabilities based on the principles of cyber security and defense.